A STANDARD COST PROBLEM. - Gibson, J. C. (The Accounting Review, 1927)
Abstract Standard costs are the natural outgrowth and development of budgetary accounting, which, curiously enough, warn first used by industry in connection with factory burden. Gathering refinements along its path, the system has reached its present stage of development in connection with manufacturing after a complete circuit of functional application. That the subject is an important one is evidenced by the fact that considerable time has been devoted to it at each of the last five annual meetings of the National Association of Cost Accountants. That it presents many controversial features is likewise apparent from even a brief study of the limited available literature, and the ultimate solutions of these problems -as the thought and effort in the field progress-will doubtless differ considerably from many of the current practices. In the next decade, unquestionably, a great impetus will be given this subject by practicing cost accountants; and university instructors in this field must be prepared not only to discuss standard costs intelligently, not only to enlighten students as to the present development of the subject, but to lead the way to scientific and practical perfection of this method of cost accounting.